Asupan Makanan, Pengetahuan Gizi Ibu, dan Status Gizi Siswa Sekolah Dasar Inklusi Galuh Handayani Surabaya - Permanisuci, Prillya Indah; Soeyono, Rahayu Dewi (Jurnal Gizi dan Kesehatan Nusantara, 2021)
School-age children are the age group between 7-15 years which usually has a significant increase in the growth and development of children. But unfortunately, not all children have a good growth and development process known as children with special needs. This child has a relative disorder in the body’s metabolism that can affect his nutritional status. This study aims to determine the relationship between food intake and knowledge of maternal nutrition with the nutritional status of students at Galuh Handayani Inclusive Elementary School Surabaya. This research is a type of cross-sectional study. This research was carried out through the WhatsApp and Google Form applications. The number of samples in the study were 32 students. The instruments used include a questionnaire on the characteristics of respondents, a test of maternal nutrition knowledge, and a food record questionnaire. The Spearmann’s Rank correlation test concluded that there was no significant relationship between nutrient intake and nutritional status (p-value >0.05). The Spearmann Rank correlation test also concluded that there was no significant relationship between maternal nutritional knowledge and nutritional status (p-value >0.05).